2021
DOI: 10.3389/fped.2021.635950
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Management in Congenital Lower Urinary Tract Obstruction With and Without Prenatal Vesicoamniotic Shunt

Abstract: Purpose: Congenital lower urinary tract obstruction (cLUTO) includes a heterogeneous group of conditions caused by a functional or mechanical outlet obstruction. Early vesicoamniotic shunting (VAS) possibly reduces the burden of renal impairment. Postpartum, pediatric urologists are confronted with neonates who have a shunt in place and a potentially impassable urethra with a narrow caliber. Early management of these patients can be challenging. Here, we would like to share the approach we have developed over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This study's use of the combined pigtail + double disk device with a 100% functional rate in liveborn infants offers the novel opportunity to investigate nephropathy in boys with severe cLUTO (16). Furthermore, the secure placement of this shunt type provided reliable urinary drainage after birth as well, allowing the stabilization and growth of these small and vulnerable neonates (25).…”
Section: Discussionmentioning
confidence: 99%
“…This study's use of the combined pigtail + double disk device with a 100% functional rate in liveborn infants offers the novel opportunity to investigate nephropathy in boys with severe cLUTO (16). Furthermore, the secure placement of this shunt type provided reliable urinary drainage after birth as well, allowing the stabilization and growth of these small and vulnerable neonates (25).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, prenatally diagnosed PUV are still a negative prognostic factor regarding maintaining kidney function. It has been proven that these cases presented the most severe malformations [2,3]. Also, the analysis of long-term outcomes in these children showed that 24-45% developed renal failure in childhood or adolescence [4].…”
Section: Introductionmentioning
confidence: 91%
“…Therefore, it is necessary to monitor fluid status and electrolytes, in order to properly supplement sodium chloride if necessary and to assess kidney function and treat possible urinary tract infections (UTI). Primary valve ablation in the first 4 to 16 weeks of life through transurethral incision (TUI) is the preferred mode of management, along with administering urinary catheter drainage for at least the first 72 h [ 9 ]. The exact time point of TUI is also dependent on the size of the available resectoscope devices.…”
Section: Introductionmentioning
confidence: 99%